A Study of Mobile Augmented Reality Advertising app - Idris, Harwati; Zulkifli, Abdul Nasir; Yusoff, Fitri (2018)
There are several typical marketing and promotional tools that have been used by most printed media Microenterprises in Malaysia to spread their services and information about their products such as brochures and banners. However, there are some weaknesses of these approaches that include; the product information consisting only text and images, and also non-interactive. The aim of this paper is to provide interactive information beyond that of conventional advertising approaches. This paper introduces the mobile Augmented Reality Advertising (MARA) app for the printed media Microenterprises. A study was carried out among a sample of 60 mobile users. Descriptive statistical analysis was employed to determine the perceptions of users towards the use of the MARA app in terms of Perceived Ease of Use, Perceived Usefulness, Attitude toward Use, Informativeness and Advertising Value. The results indicated that the users highly agreed on all the measurements.